Year 7 students’ interpretation of letters and symbols in solving routine algebraic problems - Khalid, Madihah; Yakop, Faiezah; Ibrahim, Hasniza (Creative Commons License, 2020)
In this study we focused on one of the recurring issues in the learning of mathematics, which is students’ errors and misconceptions in learning algebra. We investigated Year 7 students on how they manipulate and interpret letters in solving routine algebraic problems to understand their thinking process. This is a case study of qualitative nature, focusing on one pencil and paper test, observation, and in-depth interviews of students in one particular school in Brunei Darussalam. The themes that emerged from interviews based on the test showed students’ interpretation of letters categorized as “combining” - which involved the combining of numbers during addition, “equating a letter as 1” – where a letter in any algebraic expression is considered to be equal to 1, “misconception of equal sign” – where students see equal sign as taking the value or letter which is closest to the equal sign, “inconsistency with own rule” – where students made up their own misguided rules but utilize other rules for similar situation and finally, “seeing letters as an abbreviations for objects” – where students consider the letters as representing objects.